Monday

September 1, 2014

September 1, 2014

Posted by **Anonymous** on Tuesday, January 8, 2013 at 3:41am.

sum of 2n terms = 3* sum of n terms

then

sum of 3n terms : sum of n terms = ?

- maths -
**Reiny**, Tuesday, January 8, 2013 at 8:23amgiven: sum of 2n terms = 3* sum of n terms

(2n)/2 [2a + (2n-1)d ] = 3(n/2) [2a + (n-1)d ]

2(2a + 2nd - d) = 3( 2a + nd - d)

4a + 4nd - 2d = 6a + 3nd - 3d

-2a = -nd -d

2a = nd + d

then

sum of 3n terms : sum of n terms

= sum of 3n terms / sum of n terms

= [ (3n/2) [2a + (3n-1)d ] ] / [ (n/2) [2a + (n-1)d) ]]

= 3( nd+d + 3nd-d) / (nd+d + nd-d)

= 3(4nd) / (2nd)

=12nd/(2nd)

= 6/1

or 6 : 1

**Answer this Question**

**Related Questions**

Further mathematics - An exponential sequence (GP)of positive terms and a linear...

Further mathematics - An exponential sequence of positive terms and a linear ...

maths - the sum of the 4th and 6th terms of an A.P is 42. the sum of the 3rd and...

Further mathematics - An exponential sequence of positive terms and a linear ...

Geometric - 1) The sum of last three terms of GP having n terms is 1024 time the...

algebra 2 - An arithmetic progression has 5 terms that have a sum of 200. The ...

Math - Sum of4th and the 6th terms of an a,p is 42 . While the sum of the 3rd ...

Maths - A geometric series has three terms. The sum of the three terms is 42. ...

arithmetic - the sum of the 4th and 8th terms is 10, and the sum of the 6th and ...

math - Hi. I'm having trouble with the summation of n from i=2 of ((2^n-i)(2^n...